2000
DOI: 10.1364/josab.17.000028
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of intrinsic wavelength tuning and sideband asymmetry in a passively mode-locked soliton fiber ring laser

Abstract: We have experimentally observed continuous-wavelength tuning in a passively mode-locked fiber ring laser. Depending on the polarization setting, two separated tuning ranges are observed. We show that the wavelength tuning is a result of the existence of birefringence in the laser cavity. We have also shown that the same mechanism is responsible for the power asymmetry of sidebands appearing in the soliton spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(67 citation statements)
references
References 18 publications
1
62
0
Order By: Relevance
“…These can be selected by changing the settings of the polarization controller, 1554 nm being the most stable against polarization perturbations. Such wavelength tuning in passively mode-locked fiber ring lasers was observed before in nonnanotube systems, and is usually attributed to birefringence in the fiber ring cavity [24]. When pump power increases beyond 60mW, the laser starts operating in a multi-pulse mode.…”
Section: +mentioning
confidence: 61%
“…These can be selected by changing the settings of the polarization controller, 1554 nm being the most stable against polarization perturbations. Such wavelength tuning in passively mode-locked fiber ring lasers was observed before in nonnanotube systems, and is usually attributed to birefringence in the fiber ring cavity [24]. When pump power increases beyond 60mW, the laser starts operating in a multi-pulse mode.…”
Section: +mentioning
confidence: 61%
“…1(a) are very asymmetric, which is a result of linear cavity-loss dispersion of the laser. 12 The sidebands have well-defined positions in the soliton spectrum, which are known to be determined by the cavity length and dispersion. [4][5][6][7] However, in contrast to the positions of sidebands, their spectral strengths are sensitively dependent on the pump intensity.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Based on their formula and also taking into account the cavity dispersion effect, it is found that the linear cavity loss of the laser is a sinusoidal function of the wavelength. In a previous paper Man et al have demonstrated that the experimentally observed soliton sideband asymmetry is in fact caused by this property of the linear cavity loss [10]. Although ideally due to the existence of the saturable absorber effect in the laser, under an optimized soliton operation all CW components would experience negative effective gain and therefore be suppressed, in practice if the minimum linear cavity loss position is not appropriately set and/or the pump power is strong, CW lasing can still build up and coexist with the solitons.…”
mentioning
confidence: 99%